Cold-atmospheric-plasma–induced skin wrinkle. (4th March 2021) - Zheng, Hui; Chen, Peijian; Chen, Zhitong
Abstract: The biomedical applications of cold atmospheric plasma (CAP) involve diverse multidisciplinary approaches and are based on the plasma interactions with tissues/cells and other biomaterials. Recently, we have implemented experiments for plasma-tissue interactions and first observe CAP-induced skin wrinkling behavior. The plasma-induced wrinkling behavior during the CAP interaction with a mouse's skin is explored through theoretical modeling and numerical simulation. It is found that the critical strain decreases with the increase of the elastic modulus ratio of the equivalent film-substrate model. The change of the elastic modulus ratio will lead to different surface morphology, which infers a suitable way to diagnose skin diseases. In addition, surface morphologies with similar wavelength but larger amplitude can be observed for a larger radius of curvature. These results might help the plasma community to understand the CAP-induced wrinkling phenomenon and stimulate extensive discussions on studies on plasma-tissue/biomaterials interactions.